2012
DOI: 10.1002/cssc.201100545
|View full text |Cite
|
Sign up to set email alerts
|

Selective Production of 1,2‐Propylene Glycol from Jerusalem Artichoke Tuber using Ni–W2C/AC Catalysts

Abstract: A series of Ni-promoted W(2) C/activated carbon (AC) catalysts were investigated for the catalytic conversion of Jerusalem artichoke tuber (JAT) under hydrothermal conditions and hydrogen pressure. Even a small amount of Ni could greatly promote the conversion of JAT to 1,2-propylene glycol (1,2-PG), whereas the pure W(2) C/AC catalyst resulted in the selective formation of acetol. The product distribution profiles involving the reaction temperature, time, and H(2) pressure indicated that 1,2-PG formed as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 39 publications
2
68
0
1
Order By: Relevance
“…The cost of catalysts was greatly reduced due to the convenience in the preparation and the better reusability of catalysts without decay in the performance [28,115]. The feedstock involved microcrystalline cellulose and raw biomass, in detail including corn stover [22], birch wood [24], miscanthus [119], concentrated glucose [116,120], and Jerusalem artichoke [121]. The product distributions were tuned between EG, erythritol, and hexitols by varying the ratio of tungsten and hydrogenation metals [88].…”
Section: Catalysts and Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of catalysts was greatly reduced due to the convenience in the preparation and the better reusability of catalysts without decay in the performance [28,115]. The feedstock involved microcrystalline cellulose and raw biomass, in detail including corn stover [22], birch wood [24], miscanthus [119], concentrated glucose [116,120], and Jerusalem artichoke [121]. The product distributions were tuned between EG, erythritol, and hexitols by varying the ratio of tungsten and hydrogenation metals [88].…”
Section: Catalysts and Reaction Mechanismmentioning
confidence: 99%
“…The product distributions were tuned between EG, erythritol, and hexitols by varying the ratio of tungsten and hydrogenation metals [88]. Alternatively, the dominant product was altered from EG to 1,2-PG by changing the feedstock from glucose-based biomass to fructose-rich biomass such as Jerusalem artichoke [121]. On the basis of extensive studies, the reaction route and mechanism of this process were identified [17,28,29,115,122], and reaction kinetics are preliminarily modeled for the essential reactions [123][124][125].…”
Section: Catalysts and Reaction Mechanismmentioning
confidence: 99%
“…Compared with the blank test, the yield of glycolaldehyde over tungsten compounds was increased by a factor of 4-6. According to our recent study on the conversion of differently structured sugars over W 2 C catalysts, 7 glycolaldehyde arose from C-C bond cleavage of glucose via a retro-aldol reaction pathway. Considering that hot water could promote the dissolution and hydrolysis of cellulose, with the assistance of H + , to form glucose or cellooligosaccharides, 1b,8 we propose the reaction pathway as shown in Scheme 1.…”
Section: Downloaded By Dalian Institute Of Chemical Physics Cas On 2mentioning
confidence: 99%
“…They found that WO3 crystallites efficiently promoted the hydrolysis of cellulose to sugar intermediates and also promoted the selective cleavage of the C-C bonds. Recently, Zhang and coworkers [193][194][195] extended the feedstock from microcrystalline cellulose to lignocelluloses (such as corn stalk, birch and other woody biomass) and Jerusalem Artichoke Tuber. These studies provide a better understanding of the biomass transformation.…”
Section: From Cellulosementioning
confidence: 99%